A arborização urbana como uma política publica sustentável: Um estudo do plano de arborização de Fortaleza - Albuquerque, Marina Macêdo Gomes (2018)
Urban arborization achieve a variety of roles in urban ecosystems, such as stabilization and microclimatic improvement; reduction of atmospheric, visual and noise pollution; increased of environmental quality, among others. One of the pretensions of the present work was precisely to demonstrate that, due to its innumerable benefits, the arborization, which goes beyond an aesthetic element of the city landscape, should be considered as a strategy of counties in the urban environment. The City of Fortaleza, which lost a large part of its vegetation cover (today it has only 6.7m2 of green area per inhabitant, a number still far below the minimum recommended by the World Health Organization - WHO, which is 12m2) due to accelerated urbanization, the “irrationality” in the use and occupation of the soil, environmental degradation, among many other problems, has, since 2015, a Plan of Arborization, with has short, medium and long term goals to increase the vegetal cover. The general objective of this study was to study urban afforestation as a sustainable public policy, a key issue for public management and for the wellbeing of society in a metropolitan region. For this, an extensive bibliographical and documentary research was made, as well as an interview with representatives of the public agency that performs the arborization policy in the municipality and the “Movimento Pró-Árvore”, a Non-Governmental Organization (NGO). Through the applied methodology, concepts such as urban arborization, green area, environment, public policy, etc. were presented. The norms referring to the theme were also presented at the federal, state (Ceará) and municipal (Fortaleza) levels, which allowed a more critical look at this policy implemented in the municipality. There are some actions of the PAF that already have positive effects in the city, like the "Program of Adoption of Squares and Green Areas" have been evidenced; the "Recycling Attitudes in Schools" program; the creation of the "Arborization Manual", etc., however, it was verified that there are measures, not yet implemented by the current management, considered important for this policy, such as the development of an arboreal inventory in the city; the creation of a specific body to deal with arborization in the Municipality, among others. It is concluded that, although the creation of the PAF is an excellent and primordial initiative of municipal public power, the theory is still far from reality, to be developed for adequate and sustainable arborization. In view of this, it was emphasized the need for a joint work between public authorities and citizens in order to treat urban arborization more carefully, giving it the importance and priority it deserves. It is hoped that works of this nature help in the understanding and investigation of the public policies of urban arborization, in front of all the inherent benefits.